5-Aminolevulinic Acid Lessened Growth Suppression in Snap Bean (Phaseolus vulgaris L.) Exposed to Shallow Water Table - Haris Kriswantoro; Benyamin Lakitan; Aldes Lesbani; Andi Wijaya (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Shallow water table (SWT) is an acute problem in cultivating vegetables at riparian wetland during transitional period from dry to rainy season. SWT limits volume of aerobic rhizosphere and reduces oxygen availability. Meanwhile, 5-aminolevulinic acid (ALA) has been known for its effectiveness in offsetting negative effects of abiotic stresses. The aim of this study was to evaluate effectiveness of ALA application at pre- or during continuous 20-day SWT exposure in snap bean. SWT exposures were set at depth of 5 cm (SWT-5), 10 cm (SWT-10) and 15 cm (SWT-15) below substrate surface. ALA was applied at 4 days before SWT initiation (14 DAP), mid of SWT exposure period (28 DAP), or at end of SWT exposure (38 DAP). Results of this study indicated that SWT exposure affected growth of shoots and roots, leaf water status, proline content, and SPAD value in snap bean plant. Shallowest water table (SWT-5) caused the most severe effects. Effectiveness of ALA application was depended on time difference between ALA application and onset of SWT exposure. ALA application did not significantly improve recovery of snap bean plants after SWT exposure was terminated.